1984
DOI: 10.1128/jb.158.3.1168-1171.1984
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular polysaccharide composition, ex planta nitrogenase activity, and DNA homology in Rhizobium japonicum

Abstract: The composition of the major acidic extracellular polysaccharide (EPS) of 25 strains of Rhizobium japonicum was determined. Eight strains synthesized an acidic EPS containing rhamnose and 4-0methylglucuronic acid and were closely related according to DNA homology. These same strains also expressed high levels of ex planta nitrogenase activity. Sixteen strains produced an acidic EPS containing glucose, mannose, galacturonic acid, and galactose and were also related by DNA homology. These strains developed littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…Two derivatives of this strain may exist, since we observed considerably higher intrinsic antibiotic resistances for USDA 110 than are reported for the UC Davis strain 110.SU (17). It is therefore indicated that ex planta nitrogenase activity is generally associated with the sTIl genotype, but some sTI strains can be derepressed on a-ketoglutonate or malate medium (20,38). We note that these sTII strains are appropriate candidates for molecular genetic studies of the regulation of nitrogen fixation in R. japonicum.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Two derivatives of this strain may exist, since we observed considerably higher intrinsic antibiotic resistances for USDA 110 than are reported for the UC Davis strain 110.SU (17). It is therefore indicated that ex planta nitrogenase activity is generally associated with the sTIl genotype, but some sTI strains can be derepressed on a-ketoglutonate or malate medium (20,38). We note that these sTII strains are appropriate candidates for molecular genetic studies of the regulation of nitrogen fixation in R. japonicum.…”
Section: Discussionmentioning
confidence: 57%
“…It is reported that in gluconate-glutamate media, strains THA6, USDA 115, USDA 58, USDA 140, and USDA 110 produce no nitrogenase activity ex planta, whereas strains 61A76 and USDA 76 produce high activity ex planta (20). USDA 76 is a plant passage reisolate of USDA 74 (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hollingsworth et al [16] observed the presence of glucose, galactose and mannose in EPS, which were secreted by the Rhizobium strains MI-50A, M6±7B, and IRC 253. Some strains of Bradyrhizobium japonicum (Rhizobium as identified by the authors) contained EPS having rhamnose and 4-O-methylglucuronic acid [17]. Glycosyl components of the lipopolysaccharide (LPS) of Rhizobium trifolii 4S were found to be L-rhamnose, L-acetyl D-glucosamine and N-acetyl-D-mannosamine in a 3:1:1 molar proportion [18].…”
Section: Eng Lifementioning
confidence: 97%
“…Hup + strains were confined exclusively to the latter group of strains that were characterized by type A EPS and the absence of production of rhizobitoxine. Huber et al (1984) demonstrated a strict correlation between EPS composition and DNA homology group, which was based on DNA-DNA hybridization studies by Hollis et al (1981). DNA homology groups I and la are composed of B. japonicum strains that produce the type A EPS, while DNA homology group II is composed of the strains that produce the type B EPS.…”
mentioning
confidence: 99%